Man-machine interactions 4 : 4th International Conference on Man–Machine Interactions, ICMMI 2015 Kocierz Pass, Poland, October 6-9, 2015 /: 4th International Conference on Man–Machine Interactions, ICMMI 2015 Kocierz Pass, Poland, October 6-9, 2015. ([2016]) - Unknown
No abstract available